Educational Status, Knowledge, and Families Supported with the Implementation of the Pregnancy Exercise in Pasar Minggu Health Center, Jakarta - Anita, Fransiska (Journal of Ultimate Public Health, 2018)
Background: During pregnancy a mother will experience many changes both anatomically and physiologically. Pregnancy exercise is one of the activities in the service during pregnancy or prenatal care, which aims to prepare and train the muscles so that it can be used optimally in a normal delivery. Objective: to determine the frequency distribution of pregnant women who carry pregnancy exercise, and the relationship of several factors with pregnancy exercise in Pasar Minggu Health Center period from March to June 2016. Methods: This cross sectional analytic approach, sampling study with accidental sampling method. Samples numbered 30 people which measured by a questionnaire. Data analysis was performed using univariate and bivariate using chi-square test (x2). Results: There are significant association between education (p-value = 0.003), knowledge (p-value = 0.002), support families (p-value = 0.001) with the implementation of pregnancy exercise on the mother 2nd and 3rd trimester pregnant women in the class of Pasar Minggu Health Center. Conclusion: there is a relationship between education, employment, knowledge and family support with the implementation of pregnancy exercise. However, further research needs to cover the factors related to the implementation of pregnancy exercise.